The determinants of motivational factors and employee performance amongst support staff at Universiti Malaysia Kelantan / Wan Fadzlina Wan Nasir - Wan Nasir, Wan Fadzlina (2020)
This study is an attempt to address the determinants of motivational factors and employee performance amongst support staff at Universiti Malaysia Kelantan (UMK). The study elaborates on the conceptual framework, hypotheses and research design. Relevant literatures review for the conceptual framework such as how one theorizes or logically reasonable relationship between factors that has been part of the importance of this study. Hence, it justify the importance of the conceptual framework whereby it enables the researcher to hypothesize as well as to test the relationship between the variable involved in order to expand the understanding of the related area of the research study. The dependent variables are employee performance and independent variables are work itself, recognition, monetary reward, job security. Then as a study of hypothesis testing, this focuses on the nature of a particular group relationship or on the independence of two or more factors in a scenario. After that, analysis for correlation and regression is conducted statistically. 226 respondents at UMK were selected using stratified random sampling amongst support from 20 departments from 3 campuses. From the analysis, it shows that monetary reward, job security and work environment are the most significant motivational factor that influences employee performance amongst support staff at UMK. There are also several recommendations for further research, including realistic evaluation that expected would benefit from the extension and further testing of the theory that has been developed.